Peter Delius, Laura Phillips and Fiona Rankin-Smith (eds), A Long Way Home: Migrant Worker Worlds 1800–2014 (Historia, 2021)
Migrant labour in southern Africa has long been an area of study for scholars. However what sets apart A Long Way Home: Migrant Worker Worlds 1800–2014 from other works of its kind, is its reliance on both art and scholarly essays to provide aunique historiography of the migrant labour system in southern Africa. Inspiration for the book was drawn from an exhibition at the Wits Art Museum titled “Ngezinyawo – Migrant Journeys” which was curated by one of the editors, Fiona Rankin-Smith. This book thus deviates from the current historical scholarship on migrant labour by combining a deft mix of artwork, photographs and scholarly pieces, offering a collection of 18 chapters and more than 90 works of art and photographs, which seek to add to the existing body of knowledge on the history of migrant labour by depicting the “agency and humanity in thought, action and expression” of migrant labourers, extending across a period of 300 years (p 2).
Keywords: migrant labour; South Africa; black; Marikana